The role of on-line forex traders in Ghana - Ofori, Richard Kissi (2014)
A thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration, August-2009